The world's smallest Campanulaceae: Lysipomia mitsyae sp. nov. Issue 2 (3rd May 2016) - Sylvester, Steven P.; Quandt, Dietmar; Ammann, Lolita; Kessler, Michael
Abstract: Botanists and plant morphologists have long been fascinated by how certain species can exhibit such reduced morphologies that even their identification to genus‐ or family‐level becomes difficult. Such was the case with Lysipomia mitsyae sp. nov., an exceptionally small plant discovered in the Peruvian Andes which bears lobelioid characteristics but differs in size by an order of magnitude from the current smallest members known from the entire Campanulaceae and lacks diagnostic characters allowing it to be reliably placed to genus‐level. Molecular analyses of trnL‐F, composed of a representative Lobelioideae sampling, place the samples within the genus Lysipomia, requiring that amendments be made to the description of the genus. Supplementary ITS analyses of a representative generic sampling indicate a close relationship to Lysipomia sphagnophila and L. multiflora . We here describe the world's smallest Campanulaceae, Lysipomia mitsyae sp. nov., and discuss its phylogenetic and systematic relationships to the other members of the genus. Its highly reduced morphology, which has given it status as the smallest Campanulaceae and, quite possibly, the world's smallest eudicot, is discussed in the light of current knowledge on the physiological and anatomical constraints on alpine plant growth and survival.